GIE : Guggenheim International Exhibition 1971. - Fry, Edward F.; Messer, Thomas M.; Waldman, Diane (New York : Solomon R. Guggenheim Museum, 1971)
Andre, Carl ; Buren, Daniel ; Burgin, Victor ; Darboven, Hanne ; Dias, Antonio ; Dibbets, Jan ; Riverhead (New York) ; Heizer, Michael ; Judd, Donald ; Kawara, On ; Kosuth, Joseph ; LeWitt, Sol ; Long, Richard ; de Maria, Walter ; Merz, Mario ; Morris, Robert ; Nauman, Bruce ; Ryman, Robert ; Serra, Richard ; Takamatsu, Jiro ; Weiner, Lawrence
bibliog. p. 35-38, biog., tent. op vouwbladen per kunstenaar
Guggenheim International Exhibition 1971, Solomon R. Guggenheim Museum, New York, 12.01 - 25.04.1971
Engels
kunstcatalogus
Keywords: Amerika